Clarifying the role of coastal and marine systems in climate mitigation. Issue 1 (February 2017) - Howard, Jennifer; Sutton-Grier, Ariana; Herr, Dorothée; Kleypas, Joan; Landis, Emily; Mcleod, Elizabeth; Pidgeon, Emily; Simpson, Stefanie
Abstract : The international scientific community is increasingly recognizing the role of natural systems in climate‐change mitigation. While forests have historically been the primary focus of such efforts, coastal wetlands – particularly seagrasses, tidal marshes, and mangroves – are now considered important and effective long‐term carbon sinks. However, some members of the coastal and marine policy and management community have been interested in expanding climate mitigation strategies to include other components within coastal and marine systems, such as coral reefs, phytoplankton, kelp forests, and marine fauna. We analyze the scientific evidence regarding whether these marine ecosystems and ecosystem components are viable long‐term carbon sinks and whether they can be managed for climate mitigation. Our findings could assist decision makers and conservation practitioners in identifying which components of coastal and marine ecosystems should be prioritized in current climate mitigation strategies and policies.